ИЗУЧЕНИЕ ОБРАЗНОГО СОДЕРЖАНИЯ ПРОИЗВЕДЕНИЙ НА ЗАНЯТИЯХ ПО МУЗЫКАЛЬНОМУ ИНСТРУМЕНТУ - Халилов, Ф.Н. (SCIENCE and SOCIETY, 2022)
This article is dedicated for the problem of development in future music teachers, skills of independent work and knowledge of the musical and theoretical skills necessary for the chosen professional activity.